The influence of more prevalent technology use on the tasks carried out by older employees in Germany - Weller, Sabrina Inez [Verfasser] (My University, 2013)
"The labour market of tomorrow will be determined by the transition from an industrial to a knowledge society. In this process, the accumulation of human capital becomes increasingly important whilst opportunities for low qualified staff steadily diminish. Globalisation and technological advancement result in enhanced economic participation of highly qualified staff in the form of higher wages and better employment opportunities. In the literature, this is attributed to the 'Skill Biased Technological Change' (SBTC) [Nikutowski 2007]. According to the ALM approach [Autor et al. 2003], technological change due to falling computer prices (computerisation) leads to changes in task structures which favour a trend towards routinisation (the 'routinisation hypothesis'). Alongside these developments Germany faces the challenge of demographic change, which is reflected primarily in the shrinking and ageing of the population [Siegrist et al. 2005]. Consequently, Germany anticipates a distinct decline in the number of economically active persons in the next few decades [Federal Statistical Office 2009]. From this starting point, the question derived concerns the influence of technological change on the relationship between employment (where still possible) and its compatibility with old age. The article sets out to study what influence the more prevalent use of technology has on the tasks carried out by older employees (aged 55-65). The analyses are based on data from the BIBB/IAB and BIBB/BAuA Employment Survey from the years 1979 to 1999, which enable the precise measurement of task profiles over time [Tiemann and Zopf 2010]. The work tasks carried out by older employees (aged 55-65) were studied on the basis of the 'task approach' model [Autor et al. 2003]. This approach essentially hypothesises that subsidiarities and complementarities exist between human manpower and the use of technology in the workplace, which can be modelled in terms of the employees' task structures." (Authors' abstract, BIBB-Doku)
Keywords: P 1.8 Ältere; G 2.2.1 Technologisierung; G 2.3.4 Qualifikationswandel; G 1.2.2.1 Lohn- & Tarifsysteme; Älterer Arbeitnehmer; Technischer Wandel; Qualifikationswandel; Qualifikationsniveau; Tätigkeitsfelder; Lohnentwicklung; Multivariate Analyse